THE MEANING AND SYMBOLISM OF SURAH AL-LAHAB FROM THE PERSPECTIVE OF ROLAND BARTHES' SEMIOTICS - MZ, Isniyatun Nizwah; Rohmatika, Arina; Hidayah, Nurul (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The data for this study were sourced directly from the Qur'anic text of Surah al-Lahab, complemented by interpretations from classical and contemporary Tafsir literature, including Tafsir Ibn Kathir and Tafsir al-Misbah. Data were collected through textual analysis, identifying key terms such as لهب (lahab), يدا (yadaa), سيصلى (sayaslaa), الحطب (al-hatab), and مسد (masad), which serve as signifiers. These were then analyzed using semiotic techniques to reveal their denotative meanings (